The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000348499
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Usefulness of MUC1 and MUC4 for Distinguishing between Metastatic Adenocarcinoma Cells and Reactive Mesothelial Cells in Effusion Cell Blocks

Abstract: Objective: The aim of our study was to determine the diagnostic value of MUC1 and MUC4 for distinguishing between metastatic adenocarcinoma cells (MAC) and reactive mesothelial cells (RMC) in effusion fluids. Study Design: A total of 237 cell block specimens from pleural and peritoneal effusions, including 196 malignant effusions with MAC and 41 benign effusions with RMC, were stained with antibodies against MUC1 and MUC4. Membranous staining with or without cytoplasmic staining was considered to be positive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…There was minimal consistency in sensitivity and specificity of CEA, Ber-Ep4, MOC-31, and MUC4 in distinguishing MAC from RMC as observed in various studies reported in the literature [6,8,27,28]. The sensitivity ranges from 70.0 to 100%, while the specificity ranges from 51.2 to 100%.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…There was minimal consistency in sensitivity and specificity of CEA, Ber-Ep4, MOC-31, and MUC4 in distinguishing MAC from RMC as observed in various studies reported in the literature [6,8,27,28]. The sensitivity ranges from 70.0 to 100%, while the specificity ranges from 51.2 to 100%.…”
Section: Discussionmentioning
confidence: 89%
“…These included various epithelial markers such as carcinoembryonic antigen (CEA), Ber-Ep4, E-cadherin, MOC-31, and mucins [6,8,19,21,27,28]. However, immunocytochemical staining for these epithelial markers was unable to detect cases with MAC that did not express them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cho et al [25] found that detecting the expression level of MUC1 in ascites can help distinguish between metastatic adenocarcinoma cells and reactive mesothelial cells, with a sensitivity of up to 99% and certain diagnostic value. Similar studies have reported that MUC1 immunoreactivity can be detected in ascites samples from patients with ovarian serous carcinoma and pancreatic cancer [26].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells usually lose their original arrangement patterns in cell block sections, and most may bear some overlapping features; for example, the morphology of adenocarcinoma and mesothelioma is quite similar [11,12,13]. Therefore, dependable IHC and molecular pathology results are of great value [14,15].…”
Section: Discussionmentioning
confidence: 99%